Diagnosis, differential diagnosis, and treatment for sudden sensorineural hearing loss: Current otolaryngology practices in China - Chen, Nishan; Karpeta, Niki; Ma, Xin; Ning, Xianhui; Liu, Xiaoling; Song, Jijun; Jiang, Zigang; Ma, Xiulan; Liu, Xiuli; Zhong, Shixun; Sun, Qing; Liu, Jun; et al. (Frontiers in Neurology, 2023)
Background: Although sudden sensorineural hearing loss (SSNHL) has been attempted to be understood for 70 years, diagnosis and treatment strategies still have strong heterogeneity worldwide. Aims/Objectives: To investigate the current views and clinical practices of otolaryngologists in mainland China about the diagnosis, examination, and treatment strategies of SSNHL. Material and Methods: Questionnaires were sent to registered otolaryngologists nationwide via an online questionnaire system. Results: Most otolaryngologists supported diagnostic classification via audiograms. Regional economic situation and hospital grade affected application strategies for differential diagnosis. In terms of corticosteroid therapy, 54.9% of respondents opted to discontinue the drug 5 days after systemic administration. Both intratympanic therapy and post-auricular injections were selected by more than half of respondents as initial and salvage treatments. Conclusions: Chinese otolaryngologists exhibit heterogeneity in clinical practices for SSNHL, including distinct approaches to combination therapy and local application of steroids. Significance: This study pointed out the similarities, differences, and unique strategies of Chinese doctors in diagnosing and treating SSNHL and analyzed the possible reasons to help the world understand the current otolaryngology practices in China.